2019
DOI: 10.1002/chem.201805835
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Frameworks Harness Cu Chelating and Photooxidation Against Amyloid β Aggregation in Vivo

Abstract: Recently, photooxygenation of amyloid β (Aβ) has emerged as an effective way to inhibit Aβ aggregation in Alzheimer's disease (AD) treatment. However, their further application has been highly obstructed by self‐aggregation, no metal chelating ability, and poor protein‐enrichment capacity. Herein, porphyrinic metal–organic frameworks (PMOFs) are utilized as a superior CuII chelating and photooxidation agent for inhibiting Aβ aggregation. We selected only four classical kinds of POMFs (Zr–MOF, Al–MOF, Ni–MOF, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 61 publications
0
67
0
Order By: Relevance
“…Furthermore, the photooxygenation of Ab was investigated by using 2,4-dinitrophenylhydrazine (DNPH), a sensitive reagent for carbonyl groups of protein samples. 7,47 As shown in Fig. 3b and S12, † only the carbonyl modication in Ab samples prominently increased aer preincubation of Ab, BSA, and HSA with the PKNPs, respectively.…”
Section: Resultsmentioning
confidence: 83%
“…Furthermore, the photooxygenation of Ab was investigated by using 2,4-dinitrophenylhydrazine (DNPH), a sensitive reagent for carbonyl groups of protein samples. 7,47 As shown in Fig. 3b and S12, † only the carbonyl modication in Ab samples prominently increased aer preincubation of Ab, BSA, and HSA with the PKNPs, respectively.…”
Section: Resultsmentioning
confidence: 83%
“…The untreated CL2006 nematodes completely paralyzed and died within 11 d, while CPDs treatment attenuated Aβ‐induced toxicity and postponed the complete death to 17 d (Figure 6c). The lifespan increase was comparable to or superior over those with other nano‐agents, such as Hf‐metal–organic frameworks (Hf‐MOFs), BP@BTA (BP: black phosphorus, BTA: 4‐(6‐methyl‐1,3‐benzothiazol‐2‐yl)phenylamine), and UCNP@C 60 ‐pep (UCNP: upconversion nanoparticle, pep: Aβ‐target peptide KLVFF), [ 17,85,86 ] which extended lifespan of CL2006 strain by 3, 4, and 5 days, respectively. The results demonstrated the potential of CPDs as a potent in vivo scavenger and detector targeting the Aβ 42 deposits.…”
Section: Resultsmentioning
confidence: 99%
“…The LPFFD-modified Hf-MOFs can alleviate Aβ toxicity and lengthen the lifespan of C. elegans CL2006, which is a model animal of AD. This work cast insights into the specially-designed MOFs as neurotoxic-metal chelating and PDT agent (Yu et al, 2019).…”
Section: Vis Excitation-based Photoactive Agentsmentioning
confidence: 98%
“…In 2019, we synthesized β-NaYF4:Yb/Er@SiO 2 @RB by conjugating UCNPs with rose Bengal to degrade preformed Aβ aggregates under a 980 nm NIR light. The results revealed that UCNPs could effectively photo-degrade Aβ42 fibrils, which demonstrated UCNP's potential application in the treatment of amyloid diseases (Yu et al, 2019 ). The development of NIR photosensitizers for degenerative disease is just in its infancy.…”
Section: Nir Excitation-based Photoactive Agentsmentioning
confidence: 99%